IBNUL-MUKAFFA AND THE FACTORS CAUSED HIS DEATH - KUYANAY, Mehmet (Atlas Journal, 2022)
ABSTRACT The role and contribution of Ibnu’l-Mukaffa in Arabic literature and Islamic sciences has been discussed until today. The truth or falsity of these claims will lead us to a different point, rather than an ordinary misinformation. Is Ibnu’l-Mukaffa’ a reformist trying to reform the society or a propagandist trying to impose his own religion and culture on Muslim society and sabotaging them? .Although he does not have such an identity, is he just an ordinary civil servant trying to look good to politicians and statesmen for his own benefit? In order to find the answers to these questions, it will be illuminating to know the reason why he was killed.An in-depth study of his works can provide answers to these questions. Researching and thinking about the content of the works he translated and from which culture he got it can also illuminate the subject. .For example, the answer to the questions of whether the translation of works related to Kelile and Dimna and Persian history and rulers developed in a natural course or was it an effort to impose Indian and Persian culture on Islamic culture will be more enlightening. In this study, the scientific and literary personality of Ibnu’l-Mukaffa, as well as the religious and political factors that caused his murder, were examined